Water, Socioeconomic Factors, and Human Herpesvirus 8 Infection in Ugandan Children and Their Mothers - Mbulaiteye, Sam M.; Biggar, Robert J.; Pfeiffer, Ruth M.; Bakaki, Paul M.; Gamache, Christine; Owor, Anchilla M.; Mbidde, Edward Katongole; Ndugwa, Christopher M.; Goedert, James J.; Whitby, Denise; Engels, Eric A. (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2005)
Human herpesvirus 8 (HHV-8) infection is common in sub-Saharan Africa, but its distribution is uneven. Transmission occurs during childhood within families by unclear routes.We evaluated 600 Ugandan children with sickle cell disease and their mothers for factors associated with HHV-8 seropositivity in a cross-sectional study. HHV-8 serostatus was determined using an HHV-8 K8.1 glycoprotein enzyme immunoassay. Odds ratios for seropositivity were estimated using logistic regression, and factor analysis was used to identify clustering among socioeconomic variables.One hundred seventeen (21%) of 561 children and 166 (34%) of 485 mothers with definite HHV-8 serostatus were seropositive. For children, seropositivity was associated with age, mother's HHV-8 serostatus (especially for children aged 6 years or younger), lower maternal education level, mother's income, and low-status father's occupation (P < 0.05 for all). Using communal standpipe or using surface water sources were both associated with seropositivity (OR 2.70, 95% CI 0.80-9.06 and 4.02, 95% CI 1.18-13.7, respectively) as compared to using private tap water. These associations remained, albeit attenuated, after adjusting for maternal education and child's age (P = 0.08). In factor analysis, low scores on environmental and family factors, which captured household and parental characteristics, respectively, were positively associated with seropositivity (Ptrend < 0.05 for both). For mothers, HHV-8 seropositivity was significantly associated with water source and maternal income.HHV-8 infection in Ugandan children was associated with lower socioeconomic status and using surface water. Households with limited access to water may have less hygienic practices that increase risk for HHV-8 infection.
Keywords: Kaposi sarcoma; Africa; human herpesvirus 8; transmission; water source; environmental factors; socioeconomic factors; epidemiology